Electrochemical heavy metal detection, photocatalytic, photoluminescence, biodiesel production and antibacterial activities of Ag–ZnO nanomaterial. (October 2017) - Nagaraju, G.; Udayabhanu,; Shivaraj,; Prashanth, S.A.; Shastri, M.; Yathish, K.V.; Anupama, C.; Rangappa, D.
Graphical abstract: Highlights: For the first time reporting the ZnO and Ag–ZnO Nps through solution combustion synthesis using succinic acid as low cost novel fuel. Ag–ZnO Nps shows superior photocatalytic activity, antibacterial activity and biodiesel production compare to ZnO Nps. ZnO and Ag–ZnO Nps has been used as a electrochemical interface to detect lead and cadmium metal ions simultaneously at nano concentration level. Abstract: Zinc oxide nanoparticles (ZnO Nps) and silver doped zinc oxide nanoparticles (Ag–ZnO Nps) were prepared using nitrates of zinc and silver as oxidizers and succinic acid as a fuel through solution combustion synthesis (SCS) at 400 °C. The synthesized materials were characterized by various analytical techniques such as XRD, FTIR, Raman UV–vis, PL, SEM, EDX and TEM. The synthesized nanomaterials were tested for the photocatalytic degradation of methylene blue and the result reveal that Ag–ZnO Nps shows the better photocatalytic activity compared to undoped ZnO Nps. Biodiesel production from Simarouba oil shows that Ag–ZnO Nps acts as good catalyst compare to ZnO Nps, we have also developed sensor which showed a linearity in the concentration range 50–350 nM and limit of detection was found to be 3.5 and 3.8 nM (3 σ ) for lead and cadmium respectively. Further we have examined the antibacterial activity against Escherichia coli and Staphylococcus aureus bacteria.